Pengaruh Kesadaran Merek, E-Wom, dan Citra Merek Terhadap Niat Beli Sarung Atlas (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Purchase interest is influenced by various factors, including brand awareness, electronic word of mouth (e-wom), and brand image. This study aims to examine the effect of brand awareness, e-wom, and brand image on consumer buying interest in sarong atlas. The approach used is quantitative, with non-probability sampling techniques with a judgmental sampling strategy. Data collection was carried out on 250 respondents who had experience or knowledge of the atlas sarong, using an online questionnaire distributed via google forms. The instrument was structured using a five-point Likert scale to measure all variables. Data analysis was carried out using multiple linear regression with spss 26, preceded by classical assumption tests including normality, multicollinearity, and heteroscedasticity tests to ensure the validity of the regression model. The results showed that brand image, e-wom, and brand image have a significant positive effect on purchase intention, both partially and simultaneously. Among the three variables, e-wom has the strongest influence, followed by brand image and brand awareness. The findings imply that companies should strengthen their branding strategies, effectively utilize digital platforms for e-wom, and maintain a positive brand image to increase consumer purchase intention. This research contributes to the understanding of consumer behavior in the context of traditional clothing products.